2004
DOI: 10.1074/jbc.m405339200
|View full text |Cite
|
Sign up to set email alerts
|

Hydroperoxy Fatty Acid Cycling Mediated by Mitochondrial Uncoupling Protein UCP2

Abstract: Using Escherichia coli-expressed UCP2 reconstituted into liposomes we found that LAOOH induced purine nucleotide-sensitive H ؉ uniport in UCP2-proteoliposomes with higher affinity than LA (K m values 97 M for LAOOH and 275 M for LA). In UCP2-proteoliposomes LAOOH also induced purine nucleotide-sensitive K ؉ influx balanced by anionic charge transfer, indicating that LAOOH was also transported as an anion with higher affinity than linoleate anion, the K m values being 90 and 350 M, respectively. These data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 59 publications
6
72
0
1
Order By: Relevance
“…An uncoupling activity of UCP2 was initially proposed because of UCP2 similarity with UCP1 but still remains controversial (39)(40)(41)(42)(43). In the present study, UCP2 overexpression did not uncouple oxidative phosphorylation as shown by the maintained membrane potential, respiratory control, and P/O ratios.…”
Section: Discussionmentioning
confidence: 42%
“…An uncoupling activity of UCP2 was initially proposed because of UCP2 similarity with UCP1 but still remains controversial (39)(40)(41)(42)(43). In the present study, UCP2 overexpression did not uncouple oxidative phosphorylation as shown by the maintained membrane potential, respiratory control, and P/O ratios.…”
Section: Discussionmentioning
confidence: 42%
“…Finally, we propose that these data enhance our understanding of how the mitochondria function as a cellular rheostat balancing cellular prosurvival and cell death homeostatic programs. However, it should be noted that the roles of the various mitochondrial uncoupling protein homologues are still being investigated and have a multitude of metabolic and signaling effects, (22,37,38) that have not been investigated in this study but may contribute to their role in cellular protection.…”
Section: Discussionmentioning
confidence: 99%
“…HNE forms stable adducts with proteins so this kind of interaction with UCP would not be reversible, but specific HNE adducts of UCPs have not been detected thus far. Interestingly, in the case of hydroperoxy fatty acids, which are also lipid peroxidation products, a classical cycling mechanism of UCP action has been proposed (Jaburek et al 2004). …”
Section: Discussionmentioning
confidence: 99%